Heat transfer reduction in buildings by embedding phase change material in multi-layer walls: Effects of repositioning, thermophysical properties and thickness of PCM. (1st September 2019) - Li, Z.X.; Al-Rashed, Abdullah A.A.A.; Rostamzadeh, Mahfouz; Kalbasi, Rasool; Shahsavar, Amin; Afrand, Masoud
Highlights: The presence of PCMs reduces temperature fluctuations and heat transfer to the room. Performing sensitivity analysis for HTR based on variation in properties. Thermal conductivity of PCM plays most significant role in selecting the appropriate PCM. For equal thermal conductivity, closer melting point to room temperature is preferred. When PCM is closer to the exterior, a larger portion of it melts, HTR is greater. Abstract: Passive latent heat thermal energy storage approach incorporating phase change materials (PCM) is a brilliant technique to tackle high energy consumption issue in buildings. This paper investigated the thermal performance of the conventional walls of buildings in Isfahan, Iran with the inclusion of thirteen different phase change materials. The studied base wall was composed of plaster (2 cm), clay brick (15 cm), and cement (3 cm). The effect of PCM position inside the wall on the heat transfer was assessed in two scenarios, namely: close to the interior and close to exterior. The nonlinear governing equations were solved using the finite volume method. The results show that the performance of PCM-based wall is strongly influenced by the thermal conductivity, phase-change enthalpy and melting temperature of PCM. A PCM can more efficiently reduce the heat transfer to the interior space in case it has a lower thermal conductivity, has a higher latent heat of phase-change, and its phase-change temperature is closer to the room temperature. Moreover, the thermal conductivity has priority over other PCM thermophysical properties. The lower PCM thermal conductivity leads to transfer the lower amount of heat to the interior space. A two-fold increase in the thickness of the PCM leads to less than a twofold reduction in the heat transfer. Among the studied PCMs, the heat transfer reduction by Enerciel 22 was within the range 15.6–47.6%, while this range was 2–7.8% for CaC l 2 . 6 H 2 O .